The Comparative Study of Speaking Skill Taught by Using Grammar Translation Method And Direct Method at Sibling English Course - Ninik Farikha (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2022)
This research is aimed at describing whether there is any positive significant difference between grammar translation method and direct method at Sibling English Course, and which one is more effective taught speaking skill by using grammar translation method and direct method at Sibling English Course. The research design used was comparative study design. The subject of research was 30 students. The instrument used was test. The result of this study showed that ttest is 6.960. It is higher than t table at either 5% or 1% significance level. So, it can be concluded that teaching speaking by using direct method is more effective, and there is any positive significant difference between grammar translation method and direct method at Sibling English Course. It is recommended for the teacher to teach students’ skill using these methods.